2016
DOI: 10.1021/acs.chemrev.6b00437
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Sensitive and Surface-Specific Ultrafast Two-Dimensional Vibrational Spectroscopy

Abstract: Ultrafast two-dimensional infrared spectroscopy (2D IR) has been advanced in recent years toward measuring signals from only a monolayer of sample molecules at solid-liquid and solid-gas interfaces. A series of experimental methods has been introduced, which in the chronological order of development are 2D sum-frequency-generation (2D SFG), transmission 2D IR, and reflection 2D IR, the latter in either internal, attenuated total reflection (ATR), or external reflection configuration. The different variants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
146
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(152 citation statements)
references
References 497 publications
(1,872 reference statements)
0
146
0
1
Order By: Relevance
“…A comprehensive review on time-resolved SFG can be found in the literature 27 as well as a review on 2D vibrational spectroscopies at surfaces. 28 Note that, additionally, there exists a wealth of literature reporting studies using bulk-sensitive techniques of the dynamics of confined, non-bulk-like water in reverse micelles (see, e.g., refs (2932)).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review on time-resolved SFG can be found in the literature 27 as well as a review on 2D vibrational spectroscopies at surfaces. 28 Note that, additionally, there exists a wealth of literature reporting studies using bulk-sensitive techniques of the dynamics of confined, non-bulk-like water in reverse micelles (see, e.g., refs (2932)).…”
Section: Introductionmentioning
confidence: 99%
“…By correlating vibrational signals of an excitation and a detection frequency, the coupling between oscillators 20 and the dynamics of energy transfer 21 or chemical exchange 22 have been resolved with sub-picosecond temporal resolution. 2D IR has been technologically advanced in recent years to also enable investigations of only monolayers of sample molecules at surfaces and interfaces 16,23–28 . Particularly for adsorbates, the observation of different types of interactions is extremely valuable, since the associated dynamics may be used to extract information about molecular conformations and intermolecular distances under the influence of spatial confinement 19 …”
Section: Introductionmentioning
confidence: 99%
“…Here, we employ 2D attenuated total reflectance (ATR) IR spectroscopy 16,31,34 in combination with isotope-labelling of adsorbates at metal-liquid interfaces to investigate intermolecular interactions between diatomic molecules as well as substrate-adsorbate interactions. For this purpose, we employ 12 C 16 O/ 13 C 18 O mixtures of carbon monoxide and 12 C 14 N − / 13 C 15 N − mixtures of cyanide adsorbed to a thin Platinum (Pt) layer.…”
Section: Introductionmentioning
confidence: 99%
“…Second-order (or even-order, in general) nonlinear effects are advantageous for studying surfaces and interfaces [11]. The even-order susceptibility is zero in the bulk of a fluid, and hence only the molecules in the optically anisotropic interfacial layer contribute to the signal, in particular when the molecules at the interface are oriented in a certain manner.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the signal of even-order methods is highly surface-specific, while methods utilizing odd-order effects like infrared absorption and Raman scattering may be biased by signals from the bulk. Second-order vibrational spectroscopy can, for instance, be performed in terms of sum-frequency generation (SFG) [11,12]. However, when the IR radiation must travel through a highly absorbing medium like water, the resulting signal levels may be low.…”
Section: Introductionmentioning
confidence: 99%